2014
DOI: 10.14314/polimery.2014.585
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles in isotactic polypropylene (iPP). Part I. Silver nanoparticles as metallic nucleating agents for B-iPP polymorph

Abstract: Isotactic polypropylene (iPP) nanocomposites containing 0.1, 0.2, 0.4 and 0.6 wt % of silver nanoparticles (nAg) were prepared by melt compounding in a one-screw extruder. Selected samples were isothermally recrystallized at different temperatures 50, 75, 100, 125, 130 and 135 °C, and under non-isothermal conditions. The size of the silver particles dispersed in the iPP matrix were estimated by ultraviolet/visible spectroscopy (UV-VIS). The effects of nAg additions on the structure of the iPP were studied by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…In previous literature, various β ‐NAs have been reported, such as: γ ‐quinacridone E3B, Indigosol Grey IBL and Cibantine Blue 2B pigments, calcium salts of suberic or pimelic acid, calcium tetrahydrophthalate, dicyclohexylterephthalamide, p ‐cyclohexylamidecarboxybenzene, the most commonly used N , N ′‐dicyclohexylnaphthalene‐2,6‐dicarboxamide and others …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous literature, various β ‐NAs have been reported, such as: γ ‐quinacridone E3B, Indigosol Grey IBL and Cibantine Blue 2B pigments, calcium salts of suberic or pimelic acid, calcium tetrahydrophthalate, dicyclohexylterephthalamide, p ‐cyclohexylamidecarboxybenzene, the most commonly used N , N ′‐dicyclohexylnaphthalene‐2,6‐dicarboxamide and others …”
Section: Introductionmentioning
confidence: 99%
“…In previous literature, various -NAs have been reported, such as: -quinacridone E3B, Indigosol Grey IBL and Cibantine Blue 2B pigments, 12 -16 calcium salts of suberic or pimelic acid, 17 -19 calcium tetrahydrophthalate, 20 dicyclohexylterephthalamide, 21 p-cyclohexylamidecarboxybenzene 22 , the most commonly used N,N ′ -dicyclohexylnaphthalene-2,6-dicarboxamide 23 and others. 24 -31 Polyhedral oligomeric silsesquioxanes (POSSs) are hybrid organic-inorganic nanosized fillers and modifiers widely used for polymer modification. 32 -37 Numerous studies of the application of silsesquioxanes as NAs for iPP have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The present article is a continuation of our previous study published as Part I [20]. The aim of this study was to check the above mentioned hypothesis and show the possible arrangements of iPP chains on the surface of silver.…”
Section: Nanocz¹stki Srebra W Izotaktycznym Polipropylenie Cz II Mmentioning
confidence: 61%
“…On the other hand, a comparison of the distances between the chains arranged in the (001) plane in the a form and the lengths of multiplicity of the parameter a of silver unit cell, the conditions for epitaxy are also satisfied. Experimental data presented in [20] showed that besides the majority of b iPP the samples studied contained about 30 % of a form. However, it is well known that a iPP can be formed with no need of any additives.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation